Detection of a pinhole‐sized bronchoesophageal fistula under bronchoscopic autofluorescence imaging. Issue 13 (18th May 2021) - Morikawa, Kei; Izawa, Naoki; Kida, Hirotaka; Handa, Hiroshi; Inoue, Takeo; Mineshita, Masamichi
Abstract: Autofluorescence imaging (AFI) is a technique for detecting early‐stage lung cancer by amplifying the difference in autofluorescence of the bronchial mucosa. However, there are few reports detailing its other applications. Here, we report the case of a 54‐year‐old woman with stage IVa esophageal cancer who completed chemoradiation therapy, but developed a bronchoesophageal fistula at the left main bronchus and underwent fasting treatment. Computed tomography confirmed that the fistula had closed; however, she subsequently developed aspiration pneumonia and underwent bronchoscopy for confirmation. Although it was difficult to identify the site of the pinhole bronchoesophageal fistula under white light, AFI could easily identify the fistula and digestive mucus in light magenta. AFI may therefore be worth considering for the detection of pinhole bronchoesophageal fistulas. Abstract : Autofluorescence imaging makes it possible to easily detect pinhole‐sized tracheoesophageal fistulas.